A Structured Approach to Organizational Website Development and Usability Measurement Using the Modified System Usability Scale - Satria Vinza Hedi; Cintya Hedi Amelia Bella (IJCONSIST JOURNALS, 2025)
The increasing demand for accessible and up-to-date digital identity has encouraged organizations to adopt websites as a primary information platform. However, limited technical resources often hinder effective content management. This study proposes a structured approach to developing an organizational website using the Waterfall model and evaluates its usability through the System Usability Scale (SUS). The development process consists of five stages: communication, planning, modelling, construction, and deployment. Requirements were collected through semi-structured interviews with organizational stakeholders, resulting in the decision to implement a web-based system using a Content Management System (CMS) to ensure ease of maintenance. After deployment, usability testing was conducted using Modified SUS with a Likert scale of 1–5, involving five respondents instead. The evaluation produced an average score of 4.6, indicating that the system is highly acceptable and easy to use, although suggestions were made to improve dashboard terminology and add a search feature. The results demonstrate that a structured web development approach combined with CMS integration can effectively empower non-technical users in managing digital content. Future development may include interface personalization and multi-admin features to further enhance usability.